The characterization of mecA Gene and SCCmec typing in clinical samples of MRSA / Siti Aisya Aswani and Aziyah Abdul-Aziz - Aswani, Siti Aisya; Abdul-Aziz, Aziyah (Universiti Teknologi MARA, 2019)
MRSA is a major pathogen worldwide and its infections are associated with increased morbidity and mortality, in comparison with other S. aureus infections. The study was designed to characterize the mecA gene and staphylococcal cassette chromosome (SCCmec) in methicillin resistance S. aureus (MRSA). A total of 20 presumptive S. aureus strains were collected from one of the teaching hospitals in Selangor. Using standard biochemical tests, all the isolates were verified as S. aureus. When tested against cefoxitin, 80% of the isolates were confirmed as MRSA. All the MRSA isolates were further subjected to polymerase chain reaction (PCR) to detect the presence of mecA gene. Nine out of the 16 MRSA isolates (56%) were mecA positive, whereas the remaining four were mecA negative. The 16 MRSA with positive mecA gene were further subjected to SCCmec typing of type I, II, III, IV and V. The most frequent SCCmec types were type III (56%) followed by type II (33%), and type IV (11%). None of the isolates were of SCCmec type I or V. Our study indicates that SCCmec type III is predominant among the isolates which is in agreement with other studies conducted on clinical strains of MRSA.